Effectiveness of Responsibility Model for Personal and Social Development in Physical Education - Salamuddin, Norlena (2001)
An experiment to assess the effects of the responsibility model on students' personal and social development was conducted in a school in Shah Alam, Selangor. Instruction using the specific teaching strategies served as the intervention programme, and a pre test-post test control group research design was utilised. The study involved 146 Form One students (75 males and 71 females) in four classes. The teaching of personal and social development in physical education classes used the responsibility model developed by Hellison (1985) and adapted to Malaysian physical education curriculum. It was hypothesised that the responsibility model would improve students' personal and social development and would assist students in responding to sports and non-sports related dilemmas. It was further hypothesised that gender and level of competition did not have any influence on the-students' ability to respond to dilemmas. The hypotheses of the study received significant support. Students in the experimental group improved significantly after exposure to the responsibility model. Gender and number of years in competitive sports had no effect on the ability to adapt to the responsibility model. The implication of the study showed that the responsibility model did influence students' personal and social development. Therefore, it is recommended that specific teaching strategies be used in teaching physical education so that the aim of producing students who are able to choose right from wrong and good from bad be no longer taken for granted.